Aspects of strategic bidding in deregulated power markets - Song, Kai. (2008)
The objective of this research work is to study some aspects of the strategic bidding in a deregulated environment, which is defined as the behavior that a power producer bids other than marginal cost in an effort to increase its profits. The studies are carried out from the viewpoint of a power producer under two categories of strategies. The first is to investigate the possible benefits derived by power producers because of the market power created by adjusting operational parameters to maximize their benefits. The second is to develop the bidding strategies for power producers to make optimal decisions on generation scheduling and dispatch.